Self-assembled BiVO4 nanorods: A fascinating electrode material for highly efficient pseudocapacitors and electrochemical nitrite sensors. (March 2022) - Shafi, Imran; Liang, Erjun; Li, Baojun
Abstract: The design of new assembles at nanoscale is vital in promoting the energy - power density of storage devices. Herein, we have reported the excellent electrochemical properties of novel self - assembled BiVO4 nanorods fabricated by hydrothermal route. The as prepared self - assembled BiVO4 nanorods loaded electrode is probed under various electrochemical characterizations in aqueous electrolyte (2 M NaOH) and found that the electrode has delivered very high capacitive charge storage of 90% (which is analyzed first time for BiVO4 nanostructures) at a scan rate of 100 mV s −1, very high specific capacitance (798 F g −1 at 1 A g −1 and 866 F g −1 at 10 mV s −1 respectively) and excellent cyclic retention (89% of the initial capacitance after 4000 cycles). The self - assembled BiVO4 nanorods based asymmetric supercapacitor configuration has exhibited an extended potential window and demonstrated 98% of the capacitive charge storage, very high specific energy and power density (106 Wh kg −1 and 4200 W kg −1 respectively). Furthermore, as prepared self - assembled BiVO4 nanorods modified electrode tested for nitrite sensing in water based solution (0.1 M PBS) prove highly sensitive and selective sensor which exhibited a higher sensitivity of 56 μA μM −1 cm −2 in the wider range from 1 to 30, 000 μM (R 2 = 0.99923). The promising electrochemical properties of the electrode can be attributed to the faster ionic insertion/desertion in novel self - assembled BiVO4 nanorods by increase in the number of pore sites due to the presence of ultrafine nanoparticles in basic assembly. This work paves a way for the enhancement of electrochemical performances of energy storage devices. Highlights: The self - assembled BiVO4 nanorods with excellent electrochemical capacitive properties are synthesized by a facile hydrothermal route. The presence of ultrafine BiVO4 nanoparticles in the basic assembly of the self - assembled BiVO4 nanorods has increased the BET surface area up to 495 m 2 g −1 . Very high capacitive charge storage capacity (89% and 98% at 100 mV s −1 ) is displayed by the self - assembled BiVO4 nanorods electrode and supercapacitor respectively. Exceptionally high specific capacitance of 798 F g −1 at 1 A g −1 and 866 F g −1 at 10 mV s −1 respectively are delivered by the electrode loaded with self - assembled BiVO4 nanorods. The self - assembled BiVO4 nanorods based asymmetric supercapacitor have delivered very high energy and power densities of 106 Wh kg −1 and 4200 W kg −1 respectively. Excellent cyclic retention (89% of the initial value after 4000 cycles) is obtained. The self - assembled BiVO4 nanorods modified electrode exhibited a high nitrite ion sensitivity of 56 μA μM −1 cm −2 in the wider range from 1 to 30, 000 μM (R 2 = 0.99923).